Penerapan Model Pembelajaran Inquiry Berbantuan Geogebra untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Hidayat, Amam Taufiq (Universitas Nusa Cendana, 2025)
This study aims to improve students' mathematical problem-solving abilities through the implementation of the inquiry-based learning model assisted by Geogebra on the topic of polyhedral geometry at MTsN 2 Aceh Utara. This research employs a quasi-experimental approach with a Nonequivalent Control Group Design. The research sample consists of two classes: Class VIIIA as the experimental group, which received the inquiry-based learning model assisted by Geogebra, and Class VIIIG as the control group, which used conventional learning methods. Data were collected through pretests and posttests consisting of five questions measuring students' mathematical problem-solving abilities. The results show that the experimental class experienced a significant improvement compared to the control class, as reflected in the higher N-Gain score in the experimental class (0.59) compared to the control class (0.26). Statistical tests also indicate a significant difference in the improvement of mathematical problem-solving abilities between the two groups (Sig. = 0.000). Thus, the implementation of the inquiry-based learning model assisted by Geogebra enhances students' mathematical problem-solving abilities better than conventional learning methods on the topic of polyhedral geometry